Effect of mulch and liquid organic fertilizer on shallot production (Allium cepa) - Nasrullah, Nasrullah; Sriwati, Rina; Sugianto, Sugianto; Samadi, Samadi; Pratama, Said Mirza; El Ryiad, Kevin Rizqullah (Universitas Syiah Kuala, 2025)
Shallot (Allium cepa) is an economically valuable and highly nutritious crop whose productivity can be increased through optimal cultivation practices. This study investigated the combined effects of mulch and liquid organic fertilizer (LOF) on onion yield and performance. A factorial randomized block design (RCBD) was used consisting of two factors, namely mulch type (no mulch, black and silver plastic mulch, rice husk mulch, and shallot skin mulch) and LOF dosage (no LOF, 1,000 L/ha, and 1,500 L/ha). Data were analyzed using Least Significant Difference (LSD) and Duncan's Multiple Range Test (DMRT) at = 5%. The application of rice husk mulch and LOF at a dose of 1,500 L/ha resulted in the highest number of bulbs, bulb diameter, wet weight, dry weight, soil microbial population, and peroxidase enzyme activity among all treatments. This study demonstrates that rice husk mulch and LOF at a dose of 1,500 L/ha can significantly enhance shallot production. Additionally, the findings indicate that the use of rice husk mulch and LOF at a dose of 1,500 L/ha can boost soil microbial population and increase peroxidase enzyme activity.